Specific protein methylation defects and gene expression perturbations in coactivator-associated arginine methyltransferase 1-deficient mice - Yadav, Neelu (National Academy of Sciences, 2003)
Arginine methylation has been implicated in the regulation of gene expression. The coactivator-associated arginine methyltransferase 1 (CARM1/PRMT4) binds the p160 family of steroid receptor coactivators (SRCs). This association enhances transcriptional activation by nuclear receptors. Here, we show that embryos with a targeted disruption of CARM1 are small in size and die perinatally. The methylation of two known CARM1 substrates, poly(A)-binding protein (PABP1) and the transcriptional cofactor p300, was abolished in knockout embryos and cells. However, CARM1-dependent methylation of histone H3 was not observed. Furthermore, estrogen-responsive gene expression was aberrant in Carm1(–)(/)(–) fibroblasts and embryos, thus emphasizing the role of arginine methylation as a transcription activation tag. These findings provide genetic evidence for the essential role of CARM1 in estrogen-mediated transcriptional activation.